From economy to society? perspectives on transnational risk regulation - Lange, Bettina; Thomas, Dania, 1967-; Sarat, Austin (Bingley, U.K. : Emerald, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity?Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks.
After a romantic aspiration to society : harnessing the regulatory capacity of a social sphere / Bettina Lange -- Polanyi in an hourglass : the two lives of a sociological classic / Sabine Frerichs -- A systems theory perspective on Polanyi's great transformation / John Paterson -- From Polanyi to discourse theory / Bettina Lange -- How markets work : the lawyer's version / W. Mark C. Weidemaier, Mitu Gulati -- Sovereign debt restructuring in the Eurozone : a Polanyian reading of private law enforcement / Dania Thomas -- Defiance in the social sphere : the complexity of risk regulation in the case of fair trade / Anna Hutchens -- "Etiquette and magic" : between embedding and embedded corporate social responsibility / Aurora Voiculescu -- Emotions and risk regulation / Susan A. Bandes -- Trust and regulation : insights from the mining industry / Petrina Schiavi -- Separate spheres? The cultural contradictions of markets / Mitchel Y. Abolafia.
Includes index.
Keywords: Law -- Administrative Law & Regulatory Practice; Law -- International; Law & society; Comparative law; International finance -- Law and legislation; Investments, Foreign -- Law and legislation; Foreign trade regulation